1994
DOI: 10.1159/000139238
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between <i>Helicobacter pylori and </i>Human Gastric Epithelial Cells in Culture: Effect of Antiulcer Drugs

Abstract: A human in vitro model to study the interaction between Helicobacter pylori and gastric epithelial cells was developed using primary cultures of gastric mucosal cells (isolated from gastric biopsies or operative specimen and maintained in culture for 2 weeks) as well as the well-differentiated human gastric carcinoma cell line HM02, the undifferentiated gastric tumour cell line HM51, and the laryngeal epithelial cell line HEp-2. Primary cultures and all cell lines were exposed to seven isolates of H. pylori is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…For this, cultures were established as indicated above using, as for MedC*, conditioned media from different sources: rat Reuber hepatoma cells (ATCC no. CRL-1600), HepG2 human hepatoma cells (HB-8065), human embryonic kidney cells HEK-293 (CRL-1573), SH-SY5Y human neuroblastoma cells (CRL-2266), CHO chinese hamster ovary cells (CCL-61), MMN02 human gastric epithelial adenocarinoma cells (Wagner et al 1994), HeLa human epidermoid carcinoma cells (CCL-2), HEC1B human endometrial carcinoma cells , and the macrophage like cell line U937 (CRL-1593.2). As shown in Fig.…”
mentioning
confidence: 99%
“…For this, cultures were established as indicated above using, as for MedC*, conditioned media from different sources: rat Reuber hepatoma cells (ATCC no. CRL-1600), HepG2 human hepatoma cells (HB-8065), human embryonic kidney cells HEK-293 (CRL-1573), SH-SY5Y human neuroblastoma cells (CRL-2266), CHO chinese hamster ovary cells (CCL-61), MMN02 human gastric epithelial adenocarinoma cells (Wagner et al 1994), HeLa human epidermoid carcinoma cells (CCL-2), HEC1B human endometrial carcinoma cells , and the macrophage like cell line U937 (CRL-1593.2). As shown in Fig.…”
mentioning
confidence: 99%
“…Human gastric epithelial cells were isolated from gastric tissue specimens obtained during gastric surgery as described recently [46,47]. Informed consent was obtained from each subject, according to the revised version of the declaration of Helsinki.…”
Section: Isolation Of Human Gastric Epithelial Cellsmentioning
confidence: 99%
“…The viability of cultured cells was assessed by trypan blue exclusion and by photometric determination of released lactate dehydrogenase (LDH) enzyme activity using a commercial test (Boehringer Mannheim). Our previous work has shown that short-term incubation (12 h) of isolated human gastric epithelial cells results in the selective attachment of gastric mucous cells, leaving the chief cells and parietal cells to be recovered from the culture medium [46]. Thus these incubation conditions enabled us to cultivate a partially enriched cell fraction of gastric mucous cells without prior use of specific cell-separation procedures.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The determination of PKC translocation in gastric HM02 cells, which are derived from a human well-differentiated mucusproducing gastric carcinoma (Wagner et al, 1994), were grown for 3 days in RPMI-1640 medium supplemented with 10% fetal calf serum (FCS) at 370C in a 5% carbon dioxide atmosphere. The cell monolayers were then kept for 1 day in FCS-free medium and trypsinated.…”
mentioning
confidence: 99%